2021
DOI: 10.1038/s41598-021-83103-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycolic acid sheet covering to prevent recurrence after surgery for spontaneous pneumothorax: a meta-analysis

Abstract: The coverage technique using absorbable mesh was first described in a European guideline published in 2015 as a preventive method for the recurrence of spontaneous pneumothorax. We performed a meta-analysis based on a literature search of primary studies that compared the postoperative recurrence rate of primary spontaneous pneumothorax between the use and nonuse of polyglycolic acid sheet coverage. Two reviewers independently selected and evaluated the quality of the relevant studies. The risk ratio in each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The PGA sheet, which is an absorbable reinforcement material, increases the physical pressure resistance by forming a barrier due to thickening of the collagen tissue during hydrolysis [23,24]. This material has been widely used in daily practice to prevent air leakage after lung surgery [25,26] and to prevent pancreatic stula after pancreatic surgery [27,28]. As there have been no experimental animal studies, the effect of PGA sheets on brosis in the gastrointestinal tract is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PGA sheet, which is an absorbable reinforcement material, increases the physical pressure resistance by forming a barrier due to thickening of the collagen tissue during hydrolysis [23,24]. This material has been widely used in daily practice to prevent air leakage after lung surgery [25,26] and to prevent pancreatic stula after pancreatic surgery [27,28]. As there have been no experimental animal studies, the effect of PGA sheets on brosis in the gastrointestinal tract is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PGA sheet used in this study is an absorbable reinforcement material that is easy to use anywhere in the body due to its thin and soft features. The PGA sheet has been reported to be more effective for preventing the postoperative complications than other reinforcing materials and has been widely used for various organs based on substantial evidence [ 14 , 15 , 18 , 19 ]. The PGA sheet has been reported to be effective in preventing air leakage after lung surgery and pancreatic fistula after pancreatic surgery by forming a barrier due to thickening of the collagen tissue associated with inflammation within a few days after surgery [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many studies tried to find risk factors related to PoR of PSP in terms of demographic variables (age, gender, and smoking) [ 2 , 15 , 16 ], pneumothorax history (large size of the first episode) [ 17 ], radiological findings (presence of a bleb or bullae on CT and diaphragmatic tenting) [ 18 , 19 ], and surgical techniques (mechanical or chemical pleurodesis, vicryl mesh, and PGA coverage) [ 2 , 4 , 7 ]. Recently, several meta-analyses reported the benefits of PGA coverage [ 20 ] and mechanical and chemical pleurodesis [ 21 ]. However, there was not much attention on the timing of PoR, and there was no risk analysis for SR. Our study showed that the SR rate was much higher in the LR group (28.6%, p < 0.05) compared with the ER group (4.8%).…”
Section: Discussionmentioning
confidence: 99%